An Analysis of Fraud and Misrepresentation of Halal Logo for Cosmetic Products in Malaysia - Intan Syafiqa Abdul Salam; Mustafa 'Afifi Bin Ab. Halim (USIM Press, 2024)
Fraud and misrepresentation of the Halal logo for cosmetic products pertains to the deceptive or misleading use of the Halal logo on cosmetic products within the Malaysian market as a predominantly Muslim country whereby the Halal certification holds religious significance for Muslim consumers. This offence raises concerns regarding the authenticity and compliance of cosmetic products with Halal standards. The misuse of halal logos and certificates such as displaying logos not accredited by JAKIM has caused confusion among Muslim consumers, leading to a decrease in trust in the Malaysian halal logo. As a result, Muslim consumers may unknowingly purchase non-halal products and potentially expose themselves to harmful ingredients. Thus, the primary objective of this research is to analyze the offences associated with the Halal logo on cosmetic products while examining the agencies and authorities involved in Halal implementation and evaluating the regulatory framework governing the issuance of Halal logos for cosmetics in Malaysia. Utilizing a qualitative method, including articles and journals, standards and regulations that existed, in addition to relevant case studies, the research was seeking in-depth understanding of Halal certification and the problem of fraud and misrepresentation of Halal logo for cosmetic products. The findings indicate consumer awareness regarding these deceptive practices is found to be limited, emphasizing the need for increased transparency and education. Hence, proposes recommendations to implement stricter regulations and enforcement mechanisms to deter and penalize fraudulent activities while protecting religious sensitivities.